THE POTENTIAL OF AN AGRICULTURAL ENTERPRISE: ESSENTIAL CHARACTERISTICS - Zhevatchenko В. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The article studies the theoretical essence of the potential as an economic category and its features in the agrarian sphere. It is noted that the importance of the agrarian sphere of the economy is determined not only by a significant share of gross production, but also by ensuring the country's food security, since it is the main food source for the population. It was found that an important role is assigned to the set of existing and potential resources of the enterprise, including production, financial, innovation, intellectual, and marketing potential. It has been studied that the components of the production potential include the system of interconnected different types of resources that are at the disposal of the enterprise or can be involved in its economic activity. At the same time, it is determined not only by their quantity and quality but also by their optimal ratio, compliance of their size and composition with the needs of the tasks to be solved. It is noted that the financial potential determines the ability to adapt to changing market conditions, generate income, attract investments and remain resilient in the face of challenges. It was established that this is a combination of all available financial resources of the enterprise and methods of their use to ensure the maximum possible financial result. It was determined that unsatisfactory state financing of innovative activities of enterprises resulted in a low level of innovative activity of agricultural enterprises of Ukraine, and the sources of financing innovative activities of agricultural enterprises are mainly their funds. It was emphasized that the lack of intellectual potential in agricultural enterprises is an obstacle to the development of innovative activities. The research emphasizes a close connection of marketing potential and the financial and production ones.